2021
DOI: 10.3390/ph14030182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red and White Ginseng Preparations on Electrical Activity of the Brain in Elderly Subjects: A Randomized, Double-Blind, Placebo-Controlled, Three-Armed Cross-Over Study

Abstract: Background: Recently, the superior efficacy of hydroponically cultivated red ginseng preparation HRG80® compared to wild growing white ginseng (WG) in preventing stress-induced symptoms related to the daily work situation of healthy subjects was reported. The aim of this study was to compare the effects of HRG80®, WG, and placebo on the electrical activity in the brain of elderly human subjects during relaxation and mental challenges. Methods: Changes in the electroencephalogram (EEG) frequency ranges of 17 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…The spectral changes in the quantitative EEG induced by HRG indicated an improvement in mood and calming effects evidenced by the modulation of β2 waves, representing changes in GABA-ergic neurotransmission. HRG attenuated δ/θ waves power, which is increasing with aging [17]. Red Ginseng preparation HRG was more active than WG in humans [17] and an animal study, where HRG induced higher excitability of pyramidal cells by modulation of ionotropic glutamate NMDA and Kainate receptor-mediated transmission at daily doses of 10 to 50 mg/kg body weight corresponding to human doses of 100-500 mg [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The spectral changes in the quantitative EEG induced by HRG indicated an improvement in mood and calming effects evidenced by the modulation of β2 waves, representing changes in GABA-ergic neurotransmission. HRG attenuated δ/θ waves power, which is increasing with aging [17]. Red Ginseng preparation HRG was more active than WG in humans [17] and an animal study, where HRG induced higher excitability of pyramidal cells by modulation of ionotropic glutamate NMDA and Kainate receptor-mediated transmission at daily doses of 10 to 50 mg/kg body weight corresponding to human doses of 100-500 mg [18].…”
Section: Introductionmentioning
confidence: 96%
“…HRG attenuated δ/θ waves power, which is increasing with aging [17]. Red Ginseng preparation HRG was more active than WG in humans [17] and an animal study, where HRG induced higher excitability of pyramidal cells by modulation of ionotropic glutamate NMDA and Kainate receptor-mediated transmission at daily doses of 10 to 50 mg/kg body weight corresponding to human doses of 100-500 mg [18].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we have demonstrated that both hydroponically cultivated red ginseng root powder HRG80 TM (HRG) and white ginseng (WG) preparations were effective in preventing and mitigating the stress-induced deterioration of cognitive functions in healthy subjects [ 16 ] and elderly patients with mild cognitive disorders [ 17 ] at daily doses of 418 mg HRG (64 mg of total ginsenosides, 1.2 mg Rg5) and 764 mg WG (19.6 mg of total ginsenosides, 0.16 mg Rg5). Both HRG and WG preparations substantially impacted brain activity, affecting various brain regions depending on the mental load during relaxation and cognitive tasks associated with memory, attention, and mental performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results of many clinical trials suggesting the beneficial effects of ginseng on stress and cognitive functions were critically reviewed in several comprehensive and systematic review articles [3,[8][9][10][11][12][13][14]. Overall, ginseng is a promising treatment for mental, industrial, and chronic fatigue [15][16][17][18][19], and for the cognitive enhancement performance of healthy subjects [6,[19][20][21][22][23][24], and patients with mild cognitive impairments [25][26][27][28][29][30][31] and/or neurological disorders [7,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%